Cusco, eternal city? The risks of uncontrolled growth - Quedena, Enrique (1996)
A distinctive feature of our main cities is the way they have been shaped in the last thirty years. Despite the presence of a large set of institutions created and disappeared to deal with the problems of urban growth and housing, in reality, these institutions have played little part in defining the urban structure. It is easier to remember them, for example, in the case of SINAMOS, trying to promote a model that was the product of spontaneous actions of the population.